Collaborative Learning for Children with Special Needs through Computer Supported Collaborative Learning at Vocational High Schools - Hendra Jaya; Sapto Haryoko; Lu’mu Lu’mu (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The objectives of this study were to determine how to apply collaborative learning model through a Computer Supported Collaborative Learning (CSCL) approach for disabled students in vocational schools. The CSCL learning model is a combination of cooperative learning model and the use of computers and the internet as a medium in learning. With increasingly sophisticated technology, individuals in remote locations make it possible to collaborate on-line. Research in the field of Computer Supported Collaborative Learning or commonly referred as CSCL, provides a new experience that Websites is one model that can be used to improve collaboration in learning. Its use in improving collaboration in learning provides an insight that Websites are effectively applicable when it is integrated into learning. As in this study, it was concluded that Collaboration between lecturers and students in using websites provided a good relationship to the improvement of collaboration between lecturers and students. Utilization of this websites made it easy for lecturers and students to share information and interact either in personal or in groups and general. Collaboration activities were not only conducted in the campus environment but anytime and anywhere. The effectiveness and efficiency of using websites as CSCL media with some indicators obtained the assessment of very effective and very good.